Analisis Kesiapan Guru PAI Terhadap Adopsi Artificial Intelligence dalam Pembelajaran Al-Quran: Tinjauan Technology Readiness Index - Zulfikar, Muhammad; Supriadi, Udin; Surahman, Cucu (Mu'allim, 2026)
The integration of Artificial Intelligence (AI) in Islamic Religious Education (PAI) offers efficiency but sparks theological debates on scholarly authority. This study analyzes the readiness of PAI teachers for AI adoption in Al-Qur'an learning using the Technology Readiness Index (TRI). Employing a phenomenological qualitative approach, data were collected through in-depth interviews with five teachers across generations (Gen-X and Gen-Z). Reflexive thematic analysis mapped the dimensions of Optimism, Innovativeness, Discomfort, and Insecurity. The findings reveal a "Technically Ready, Spiritually Cautious" profile. All participants acknowledged AI’s administrative utility. A generational gap exists: Gen-Z is driven by innovation and high self-efficacy, while Gen-X relies on social proof. Crucially, high universal Insecurity regarding content validity and the loss of scholarly sanad (chain of transmission) was found. Teachers position AI strictly as an instrumental tool, rejecting it as a substitute for talaqqi (face-to-face learning). The study concludes that the primary barrier is theological protection, not technical incompetence. It suggests an adoption strategy focused on ethical literacy and positioning AI as a supervised assistant to maintain Islamic education's integrity. This study recommends that the Ministry of Religious Affairs and Islamic educational institutions develop AI adoption ethical guidelines that integrate artificial intelligence as an instructional assistant without undermining the supremacy of sanad and the teacher's authority in maintaining the authenticity of religious teachings.